The death of a venerable nun in 18th century Nuevo Reino de Granada (Colombia): The case of Maria Gertrudis Teresa de Santa Inés: the “Lily of Bogotá” (2009)
The Counterreformation sought to strengthen the catholic devotions that were under attack by the Protestant Reformation. Catholic spirituality reached new heights, exaggerating religious trends that started before the Council of Trent,1 specifically in relation to penitential and ascetic practices, emphasis on meditations on the Passion of Christ, Mariolatry, visionaries and mystics, and of course, the veneration of Saints. The Catholic Church found a strong ally in the Spanish Crown, and when the enterprise of conquest and colonization of the New World took place, they were side by side, conquering the lands and the souls of the native population.